Media Permainan Kotak dan Kartu Misterius (KOKAMI) untuk Meningkatkan Keaktifan Siswa Kelas VII dalam Pembelajaran Bahasa Arab - Umi Khotijah; Nisa Syuhda (Laboratorium Pendidikan Fakultas Ilmu Tarbiyah dan Keguruan, 2020)
The activeness of students in the process of teaching and learning activities needs attention so that the learning process can produce maximum results. Seeing the inactivity of class VII students of MTs Taruna al-Qur'an Yogyakarta in the Arabic language learning process initiated researchers to conduct experimental research on the use of the mysterious box and card games (KOKAMI) in the Arabic learning process which aims to determine differences in student activity between experimental groups with the control group after the application of KOKAMI media. This type of research is quasi-experimental research (Quasi-Experimental) using a quantitative approach. The research subjects consisted of class VIIA students as the experimental class and class VIIB students as the control class. The data were obtained based on the results of observations, interviews, and questionnaires which were then analyzed quantitatively descriptively using paired sample t-test and independent sample t-test with the help of SPSS16. The results showed that Arabic learning activity increased after the implementation of KOKAMI media. Based on the independent sample t-test, it was obtained a post-experimental value of 0.017 <0.05 and a post-control value of 0.017 <0.05, it can be concluded that there was a significant difference between the students' Arabic learning activeness in the experimental class and the control class. Abstrak: Keaktifan siswa dalam proses kegiatan belajar mengajar perlu mendapat perhatian agar proses pembelajaran dapat membuahkan hasil yang maksimal. Melihat kurang aktifnya siswa kelas VII MTs Taruna al-Qur’an Yogyakarta dalam proses pembelajaran bahasa Arab menginisiasi peneliti dalam melakukan penelitian eksperimen penggunaan media permainan kotak dan kartu misterius (KOKAMI) dalam proses pembelajaran bahasa Arab yang bertujuan untuk mengetahui perbedaan keaktifan siswa antara kelompok eksperimen dengan kelompok kontrol setelah diterapkannya media KOKAMI. Jenis penelitian ini merupakan penelitian eksperimen semu (Quasi Experimental) dengan menggunakan pendekatan kuantitatif. Subyek penelitian terdiri dari siswa kelas VIIA sebagai kelas eksperimen dan siswa kelas VIIB sebagai kelas kontrol. Data diperoleh berdasarkan pada hasil observasi, wawancara dan kuesioner yang kemudian dianalisis secara kuntitatif deskriptif menggunakan uji paired sample t-test dan independent sample t-test dengan bantuan SPSS16. Hasil penelitian menunjukkan bahwa keaktifan belajar bahasa Arab meningkat setelah diterapkannya media KOKAMI. Berdasarkan uji independent sample t-test diperoleh nilai post-eksperimen sebesar 0,017<0,05 dan nilai post-kontrol 0,017<0,05, maka dapat disimpulkan terdapat perbedaan yang signifikan antara keaktifan belajar bahasa Arab siswa kelas eksperimen dengan kelas kontrol.